Implementation of E-Procurement Policies Through Direct Procurement at The Bureau of Goods and Services Procurement Of Regional Secretariat Of East Java Province - Ardine, Elfrida Laras Candrakusuma; Hertati, Diana (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The achievements obtained, such as the Digital Government Award 2023 from the Ministry of Administrative Reform and Bureaucratic Reform (PANRB) in the category of Implementation of Electronic-Based Government System Services (SPBE) for Central and Regional Government Agencies (IPPD) in 2023, demonstrate that the East Java Provincial Government is an excellent example of an E-Government system implementation in Indonesia.Government to Business (G-to-B) ties are one of the features of the E-Government system, and they are demonstrated through the electronic purchase of products and services from the government (E-Procurement),t is anticipated that the digitalization of public procurement would improve implementation accountability and transparency. One method of acquiring government products and services is through Direct Procurement, which is one of the suppliers' options.As one of the Regional Work Units (SKPD) that was recently formed in 2020, the Bureau of Goods and Services Procurement of the Regional Secretariat of East Java Province is the focus of this research, which looks at how the goods and services procurement policy is being implemented through Direct Procurement. This research uses four focuses of policy implementation theory according to Richard Matland, namely: 1) The Accuracy of Policy; 2) The Accuracy of Implementation; 3) The Accuracy of Target, and 4) The Accuracy of Environment.